Reviews and syntheses: A framework to observe, understand and projectecosystem response to environmental change in the East Antarctic SouthernOcean - Gutt, Julian; Arndt, Stefanie; Barnes, David Keith Alan; Bornemann, Horst; Brey, Thomas; Eisen, Olaf; Flores, Hauke; Griffiths, Huw; Haas, Christian; Hain, Stefan; Hattermann, Tore; Held, Christoph; et al. (Biogeosciences, 2022)
Systematic long-term studies on ecosystem dynamics are largelylacking from the East Antarctic Southern Ocean, although it is wellrecognized that they are indispensable to identify the ecological impactsand risks of environmental change. Here, we present a framework forestablishing a long-term cross-disciplinary study on decadal timescales. Weargue that the eastern Weddell Sea and the adjacent sea to the east, offDronning Maud Land, is a particularly well suited area for such a study,since it is based on findings from previous expeditions to this region.Moreover, since climate and environmental change have so far beencomparatively muted in this area, as in the eastern Antarctic in general, asystematic long-term study of its environmental and ecological state canprovide a baseline of the current situation, which will be important for anassessment of future changes from their very onset, with consistent andcomparable time series data underpinning and testing models and theirprojections. By establishing an Integrated East Antarctic MarineResearch (IEAMaR) observatory, long-term changes in ocean dynamics,geochemistry, biodiversity, and ecosystem functions and services will besystematically explored and mapped through regular autonomous and ship-basedsynoptic surveys. An associated long-term ecological research (LTER)programme, including experimental and modelling work, will allow forstudying climate-driven ecosystem changes and interactions with impactsarising from other anthropogenic activities. This integrative approach willprovide a level of long-term data availability and ecosystem understandingthat are imperative to determine, understand, and project the consequencesof climate change and support a sound science-informed management of futureconservation efforts in the Southern Ocean.
CRIS-Team WoS Importer:2022-12-16